Implementasi Rescheduling, Reconditioning Dan Restructuring Sebagai Upaya Penyelesaian Pembiayaan Bermasalah Di BSI Kcp Jalan Baru Bogor - Mahardika Ramadhan; Hilman Hakiem; Amran (CV. ITTC INDONESIA, 2024)
Problematic financing that arises due to the decline in micro and small enterprises (MSEs) among customers negatively impacts the bank's financial performance, including a decrease in liquidity and the bank's reputation. Problematic financing is measured by the collectability of financing, which is divided into five categories, ranging from current to non-performing loans (NPL). This study aims to analyze the implementation of the Rescheduling, Reconditioning, and Restructuring (3R) program in handling problematic financing at Bank Syariah Indonesia (BSI) KCP Jalan Baru. The research method used is a qualitative approach with structured interviews as the data collection technique. The results of the study show that the implementation of the 3R program at BSI KCP Jalan Baru begins with the identification of customers facing payment difficulties, followed by a thorough analysis of the customers' financial conditions to determine the most appropriate solution. Customers who wish to utilize the 3R facility must meet several requirements, such as evidence of financial recovery efforts and a good payment history. BSI is considered responsive and cooperative in assisting customers throughout the process. The implementation of the 3R program has a positive impact on both customers and the bank. For customers, this program reduces the burden of payments and allows them to focus more on the continuity of their business. For the bank, the program helps reduce the Non-Performing Loan (NPL) ratio and maintains cash flow stability and financial health. However, there are also negative impacts, such as the addition of interest or restructuring fees, which increase the total installment amount for customers. The key factors influencing the success of the 3R implementation are smooth and open communication between the bank and customers, the bank's policy flexibility, the customer's financial condition, the level of openness of the customer, the customer's ability to communicate/negotiate, and the customer's good payment track record. These findings align with previous research emphasizing the importance of these factors in the success of financing restructuring programs in Islamic banking.